KONSEP PENDIDIKAN ISLAM INTEGRAL MENURUT MOHAMMAD NATSIR - Endang Endang (IAIN Ambon, 2021)
Abstract: The research entitled Concept of Integral Islamic Education According to Mohammad Natsir, aims to find out how the concept of integral education is applied by Mohammad Natsir. This type of research is library research because the data in this study were taken from library materials. This study uses several methods, including: Content, historical and descriptive. The data sources are taken through primary data and secondary data. The results obtained from this study are Mohammad Natsir's thoughts on integral education, which is an educational model that combines Islamic education and general education, this is evidenced by not contrasting the west with the east. Islam only recognizes the antagonism between right and falsehood. Everything that is right is accepted, even if it comes from the west, all that is false will be removed even if it comes from the east. With the creation of integral education, students can prioritize between spiritual and physical. The implementation of Mohammad Natsir's integral education is that the curriculum used is the national curriculum and the religious curriculum. And balance between worldly life and hereafter, balance between physical and spiritual. In public schools, Islamic Religious Education must be included in a balanced manner. Likewise, Islamic boarding schools must also include general education in a balanced way. Keywords: Islamic Education, Integral, Mohammad Natsir Abstrak: Penelitian yang berjudul Konsep Pendidikan Islam Integral Menurut Mohammad Natsir, bertujuan untuk mengetahui bagaimana konsep pendidikan integral yang diterapkan oleh Mohammad Natsir. Jenis penelitian ini merupakan penelitian studi kepustakaan (library research) karena data-data dalam penelitian ini diambil dari bahan-bahan pustaka. Penelitian ini menggunakan beberapa metode antara lain: Content, historis dan deskriptif. Adapun sumber data yang diambil melalui data primer dan data sekunder. Hasil yang diperoleh dari penelitian ini adalah pemikiran Mohammad Natsir tentang pendidikan integral adalah model pendidikan yang memadukan antara pendidikan Islam dan pendidikan umum, ini dibuktikan dengan tidak mempertentangkan antara barat dengan timur. Islam hanya pengenal antagonisme antara hak dan bathil. Semua yang hak diterima, biar pun datangnya dari barat, semua yang bathil akan disingkirkan biarpun dari timur datangnya. Dengan terciptanya pendidikan integral peserta didik dapat mementingkan antara ruhani dan jasmani. Implementasi pendidikan integral Mohammad Natsir itu adalah kurikulum yang dipakai adalah kurikulum nasional dan kurikulum agama. Serta menyeimbangkan antara kehidupan duniawi dan ukhrawi, keseimbangan antara jasmani dan ruhani. Pada sekolah umum, Pendidikan Agama Islam harus dimasukkan secara seimbang. Begitu pula dengan pesantren juga harus memasukkan pendidikan umum secara seimbang pula. Kata kunci: Pendidikan Islam, Integral, Mohammad Natsir